Home security system based on drone automation - IoT approach - Darko Kostadinov; Veno Pachovski; Irena Stojmenovska (Ss. Cyril and Methodius University in Skopje, Faculty of Computer Science and Engineering, Republic of North Macedonia, 2020)
Drones have already established a significant role in many industries. As technology progresses, in the next few years, drones will be considered useful tools for a variety of consumers. The paper aims to show the benefits and advantages of using a drone as a dynamic security camera (strengthened by using image recognition software) for home security purposes. Two applications were created as proof of concept to present the idea. This approach can be beneficial not only for home security, but also for other industries such as: cinematography, agriculture, energy, civil engineering and constructions, safety, security in general, governmental use, oil refining and other environmental sciences.
Keywords: Home security, IoT, drone, image recognition, web sockets, tensorflow.js, AWS, Node.js